Pengelolaan Sanitasi Pada Pemerintah Lokal: Studi Kasus Peningkatan Kelembagaan Prasarana Instalasi Pengolahan Lumpur Tinja Kabupaten Ponorogo - Yuanita, Mike; Syahbiba, Ismy Nur; Haryono, Nanang (Universitas Airlangga, 2021)
AbstractSanitation management is an important part of sustainability in line with the Sustainable Development Goals (SDGs). For this reason, the Directorate General of Human Settlements (IPLT) has built an infrastructure for sewage treatment plants (IPLT) in an effort to increase public access to sanitation services. For optimal and sustainable IPLT, it is necessary to separate the functions of regulator and operator managing the sanitation sector through institutional development of the technical implementing unit (UPTD). The focus of the discussion of this article is on the analysis of the institutional development of the UPTD for the management of IPLT Infrastructure in Ponorogo Regency in 2021. The results of the research are that institutional development is running according to the SE Ministry of Home Affairs No 061/4338/OTDA concerning Consultation Guidelines for the Establishment of Branch Offices and UPTDs, however, in the consultation process for KA UPTD PALD Ponorogo Regency at the Bureau of Organization of East Java Province was delayed because of the